Truth and the Search for Truth in History: criticism of its production – an editorial contextualization - Lara, José Edson (Revista Gestão & Tecnologia, 2024)
Dear reader, Regarding truth, throughout the history of thought, it can be assumed that it has constituted the essence of the reflections of practically all philosophers, scientists and religious people. In this sense, it reveals itself as a gift, constituting the essence and eidetic of the reflections of thinkers. The processes of its incessant search are pertinent to the purposes and actions of Science.